Analysis of the Quota of Women’s Representation as Candidates for Legislative Institutions in PKPU Number 10 of 2023: (Analysis of Affirmative Action of Legislative Candidates in General Election Commission Regulation Number 10 of 2023) - Dahlia, Nelly; Warjiati, Sri (SERUNAI, 2023)
The era of reform and democratisation, as well as the implementation of regional autonomy, is an important moment for women, especially in the regions, to actively participate in determining the direction of democracy in the life of the nation and state, but until now, politicians have more often shown interests that are not related to maintaining and implementing the sacred principles of democracy and the aspirations of the people. This situation occurs in the General Election Commission Regulation number 10 of 2023 Article 8 which is deemed not to represent women’s representation. For this reason, this paper discussed women’s representation in PKPU Number 10 of 2023 in the perspective of the theory of legal norms. The research method used was a normative juridical research approach. This approach involved legal research conducted by studying statutory materials and supporting literature to answer the problems being discussed. The result of this research was that PKPU Number 10 of 2023 not only contradicted the provisions of Article 245 of Law No.7 of 2017, but also did not provide certainty for the implementation of the zipper system as stipulated in the provisions of Article 246 (2) of Law No. 7 of 2017. Empirically, women’s representation was still a problem, both in political parties and when they became legislative members.